Advances in the Biotechnological Potential of Brazilian Marine Microalgae and Cyanobacteria - Deborah Terra de Oliveira; Ana Alice Farias da Costa; Fabíola Fernandes Costa; Geraldo Narciso da Rocha Filho; Luís Adriano Santos do Nascimento (Molecules, 2020)
Due the worldwide need to improve care for the environment and people, there is a great demand for the development of new renewable, sustainable, and less polluting technologies for food, health, and environmental industries. The marine environment is one of the main areas investigated in the search for alternatives to the raw materials currently used. Thereby, cyanobacteria and marine microalgae are microorganisms that are capable of producing a diverse range of metabolites useful for their cellular maintenance, but that also represent a great biotechnological potential. Due its great potential, they have an enormous appeal in the scientific research where, the biological activity of metabolites produced by these microorganisms, such as the antioxidant action of sterols are, some examples of biotechnological applications investigated around the world. Thereby, Brazil due to its extensive biodiversity, has high potential as a raw material supplier of marine waters, researching cyanobacteria and microalgae metabolites and their applications. Thus, this rapid review intends to present some important contributions and advances from Brazilian researchers, using the biomass of Brazilian cyanobacteria and marine microalgae, in order to illustrate the value of what has already been discovered and the enormous potential of what remains unexplored so far.